2010
DOI: 10.2220/biomedres.31.27
|View full text |Cite
|
Sign up to set email alerts
|

Hair growth stimulated by conditioned medium of adipose-derived stem cells is enhanced by hypoxia: evidence of increased growth factor secretion

Abstract: Adipose-derived stem cells (ADSCs) and their secretomes mediate diverse skin-regeneration effects, such as wound-healing and antioxidant protection, that are enhanced by hypoxia. We investigated the hair-growth-promoting effect of conditioned medium (CM) of ADSCs to determine if ADSCs and their secretomes regenerate hair and if hypoxia enhances hair regeneration. If so, we wanted to identify the factors responsible for hypoxia-enhanced hair-regeneration. We found that ADSC-CM administrated subcutaneously induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 30 publications
(27 reference statements)
9
118
0
4
Order By: Relevance
“…For example, Rehman et al reported that hypoxia increased antiapoptotic and angiogenic growth factor secretion of ASC, which increased the recovery from hind-limb ischemia [11]. Our group also demonstrated that hypoxia-expanded ASCs enhanced antioxidant and angiogenic growth factor secretion to accelerate skin regeneration [8,9]. However, all those studies focused on the chronic response to hypoxia whereby stabilization of HIF-1a enhanced the secretion of target proteins and increased the regenerative potential of ASCs.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…For example, Rehman et al reported that hypoxia increased antiapoptotic and angiogenic growth factor secretion of ASC, which increased the recovery from hind-limb ischemia [11]. Our group also demonstrated that hypoxia-expanded ASCs enhanced antioxidant and angiogenic growth factor secretion to accelerate skin regeneration [8,9]. However, all those studies focused on the chronic response to hypoxia whereby stabilization of HIF-1a enhanced the secretion of target proteins and increased the regenerative potential of ASCs.…”
Section: Introductionmentioning
confidence: 59%
“…In those studies, the treatment of a conditioned medium of ASCs (ASC-CM) stimulated dermal fibroblasts and papilla cells, and ASC transplantation accelerated wound healing and hair regeneration in vivo. Of note, the hypoxia-cultured ASCs and CM induced a significant increase in wound-healing and hairgrowth potential compared with normal culture conditions [8,9]. Likewise, the beneficial effects of culturing ASC under hypoxic conditions has been reported in various experimental systems [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 86%
“…The proliferation of adipose tissue-derived stem cells (ADSCs) is elevated under hypoxic conditions as compared to normoxic conditions. In this experimental model, hypoxia enhanced the ADSC-promoted hair growth via the production/ secretion of growth factors (29). The physiological condition of the bone marrow appears to be low in oxygen tension and limited in nutrient supply.…”
Section: Discussionmentioning
confidence: 80%
“…La siguiente alternativa planteada, siguiendo la lógica como sucede con la estimulación angiogénica y fibroblástica (17,18), es que exista estimulación por efecto paracrino hacia el linaje epidérmico mediante la secreción de factores de crecimiento como el EGF, IGF, PDGF, entre otros. Más aún, está documentado el crecimiento de pelo debido a la estimulación paracrina de las ASCs (19,20).…”
Section: Discussionunclassified